Teacher-student relationship as resilience strengthener in novice teachers before and during the pandemic - Villalobos Vergara, Paula; Peña-Sandoval, César; Díaz, Romina; Barría-Herrera, Pamela (Frontiers in Education, 2024)
This article addresses the role of teacher-student relationship in novice teachers' resilience before (11 participants) and during the COVID-19 pandemic (14 participants). Employing a qualitative multi-case study, we conducted a total of 35 semi-structured interviews with these 25 novice teachers working in highly vulnerable schools in the Metropolitan Region of Chile. Drawing upon the literature on teacher resilience and the teacher-student relationship, we carried out a comparative analysis of the two groups. The findings reveal two significant connections and one tension: a positive connection between the student figure and the resilient novice teachers' identity; another positive connection between professional identity and the pedagogical relationship prioritized by resilient teachers; and a tension between the pedagogical relationship prioritized by resilient novice teachers and school leadership teams' definition of pedagogical work. These findings show how the teacher-student relationship represents the driving force of novice teachers' pedagogical work and resilience, an essential element that persists despite the abrupt changes generated by the pandemic. Implications highlight the significance of conducting further research on relational aspects of novice teachers' resilience and strengthening it through institutional support systems.